Melanoma Screening Days During the Coronavirus Disease 2019 (COVID-19) Pandemic: Strategies to Adopt - Alessia Villani; Gabriella Fabbrocini; Claudia Costa; Massimiliano Scalvenzi (Dermatology and Therapy, 2020)
Abstract Melanoma is one of the most common cancers, with an increasing incidence worldwide. Disease stage represents the most important prognosis factor; therefore, early diagnosis is essential for melanoma patients’ survival rates. Following the outbreak in China, the coronavirus disease 2019 (COVID-19) pandemic has spread all over the world and the majority of dermatological visits have been postponed. These measures could cause a delay in melanoma diagnosis and management leading to an increase of morbidity, mortality and healthcare costs. Herein we propose an alternative model of skin cancer screening and the organization of screening campaigns in order to detect malignant lesions early during this emergency period.